Application of mixed-culture with Lactobacillus brevis and Saccharomyces cerevisiae to Chinese yellow rice wine brewing for ethyl carbamate regulation. (April 2021) - Zhou, Wanyi; Shu, Qin; Zhang, Xinglin; Chen, Qihe
Abstract: Co-culturing two or more species has recently been used in fermenting foods for product flavor or safety control. Ethyl carbamate (EC) is a potential carcinogenic compound presented in Chinese yellow rice wine which can be reduced by fermentation starters modification. In this work, the effect of Lactobacillus brevis ( L. brevis ) on EC in yellow rice wine fermentation with Saccharomyces cerevisiae ( S. cerevisiae ) was studied and an optimal mixed-culture fermentation method was constructed according to comparative analyses of EC concentration and fundamental quality. EC concentration could be further reduced by 68.4% at most through adding 10 8 cfu/L L. brevis during S. cerevisiae fermentation. L. brevis also had beneficial influence on hedonic quality of yellow rice wine. Meanwhile, the effect of gallic acid on EC formation in this mixed-culture fermentation system was elucidated. Unfortunately, the coexistence of gallic acid and L. brevis attenuated their inhibitory effect on EC formation. Graphical abstract: Image 1 Highlights: Lactobacillus brevis is added to regulate EC in Chinese yellow rice wine. An optimal mixed-culture fermentation with Lactobacillus brevis is constructed. EC level can be reduced by 68.4% at most by adding 10 8 cfu/L Lactobacillus brevis. Lactobacillus brevis has beneficial influence on hedonic quality of yellow rice wine. Coexistence of gallic acid and Lactobacillus brevis attenuates their inhibitory effect on EC.